4CPS-238 Medication and confusion in acute hospital older patients. (March 2019) - Marvin, V; Ward, E; Whiting, E
Abstract : Background: Confusion is a significant problem in older patients. Studies have shown that up to one-third of older patients admitted to hospital have delirium and up to 40% have dementia. Various prescription medicines can cause confusion and may be inappropriate in the elderly, with the risk of harm outweighing potential benefits. Medication reviews, as part of comprehensive geriatric assessments, for example, aim to optimise an individual's medicines and reduce potentially inappropriate prescriptions. Purpose: This study aimed to determine the prevalence of confusion in older patients in an acute hospital and whether inappropriate medicines potentially contributed. We followed-up patients to find if they had a medication review while in hospital and if this led to deprescription of medicines that can contribute to confusion. Material and methods: We conducted a single-centre prospective observational cohort study. Patients aged 65 or older hospitalised with confusion were identified using their medical clerking notes. Medicines taken on admission to hospital were recorded and any that could contribute to confusion were identified. We determined whether the confused patients had a medication review during their admission and identified any changes to their medication list. Results: Three-hundred and ten patients aged 65 or older were admitted during the 1 month study period, 100/310 (32.3%) of whom were documented as having some degree of confusion. Thirty-eight per cent took at least one medicine that potentially contributed to confusion. Eighty-two per cent of confused patients had a medication review. Medication reviews did not appear to result in a decrease in prescriptions of medicines that contributed to confusion. Conclusion: Prescribing of medicines known to potentially cause confusion is common with more than one-thirdof those over 65 years' old and with confusion taking at least one. Further studies are needed to determine reasons for continuing or even initiating culprit medicines in this population of older patients and the impact on clinical outcomes. References and/or acknowledgements: NIHR CLAHRC NWL, Dr Iñaki Bovill, consultant physician. No conflict of interest.